The implementation optimization of school development plan in flood disaster mitigation policy in tropical rainforest (Case study at state junior high school 5 Samarinda) - Sjamsir Hasbi; Zaenab Hanim; Sani Bin Husain (Social Sciences and Humanities Open, 2023)
The purpose of this study is to describe: 1) Optimizing the conceptualization of the School Development Plan, 2) Optimizing the implementation of the School Development Plan, on flood disaster mitigation policies in a tropical rain forest at State Junior High School 5 Samarinda. This research is a case study type with qualitative-descriptive analysis. Data collection techniques using in-depth interviews, observation, and documentation. Data analysis was performed using the Miles and Huberman model.The results of the study are as follows: 1) Optimizing the conceptualization of the School Development Plan in flood disaster mitigation policies in a tropical rain forest at State Junior High School 5 Samarinda through environmental data analysis, stakeholder participation, accommodating the tropical school concept has not run optimally. 2) Optimization of the implementation of the School Development Plan in flood disaster mitigation policies in a tropical rain forest at State Junior High School 5 Samarinda has not been optimal because it has not gone through three basic mitigation programs and periodic evaluations.